METHODS FOR ESTIMATING THE INTERNAL NOISES IN AUTO COLLIMATING DEVICES: METHODS FOR ESTIMATING THE INTERNAL NOISES IN AUTO COLLIMATING DEVICES - Getsov, Petar; Stoyanov, Stiliyan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Methods for estimating the internal noises in auto collimating devices are proposed. These devices are designed for measuring of angular shifting of an object with mirror surface, able to make shifts in certain range. Auto collimating method for measuring of angles is one of the high accurate methods for solving of unique technological problems. The accuracy in angular measuring through auto columniation in laboratory conditions reaches ten parts of the second. Classification of the existing photoelectric devices, their optical schemes, main metrological characteristics and working principle are exemplified in [1, 4, 6] and others. The objective of this research is the analysis of the internal light noises in AC for measuring angular shifts of the mirror surface object, which could move freely in restricted. Generally, auto collimators (AC) consists of auto collimating lens, scale, and source of light, condenser and analyzer of visible area. The scale, together with the source of light and the photo electric analyzer are placed in the focal plane of the lens and could be separated with semitransparent mirror. Having in mind the requirements of the overall dimensions and the tendency of making them smaller, the constructor has a choice of selecting a scale, analyzer and AC lens.